2015
DOI: 10.1210/jc.2015-1967
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin (Tg) Testing Revisited: Tg Assays, TgAb Assays, and Correlation of Results With Clinical Outcomes

Abstract: Tg-IAs remain the method of choice for Tg quantitation in TgAb- patients. In TgAb+ patients with undetectable Tg by immunometric assay, the Tg-MS will detect Tg in up to 20% additional cases. The Tg-RIA will detect Tg in approximately 35% cases, but a significant proportion of these will be clinical false-positive results. The undetectable Tg-MS seen in approximately 40% of TgAb+ cases in patients with disease need further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 26 publications
5
89
1
1
Order By: Relevance
“…Interestingly, in his study, Spencer [84] showed that any detectable level of TgAb, although lower than the cutoff of positivity, has the potential to interfere with Tg measurement relative to its level. Recently, Netzel et al [85] In addition, some years ago, a paper [86] described FNA performed in two PTC patients with positive TgAb before and after rhTSH; detectable FNA-Tg levels were found only after rhTSH stimulation. The authors speculated that the Tg excess induced by rhTSH stimulation may 'saturate' all TgAb binding sites, explaining why Tg was only detectable after rhTSH stimulation in their patients.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in his study, Spencer [84] showed that any detectable level of TgAb, although lower than the cutoff of positivity, has the potential to interfere with Tg measurement relative to its level. Recently, Netzel et al [85] In addition, some years ago, a paper [86] described FNA performed in two PTC patients with positive TgAb before and after rhTSH; detectable FNA-Tg levels were found only after rhTSH stimulation. The authors speculated that the Tg excess induced by rhTSH stimulation may 'saturate' all TgAb binding sites, explaining why Tg was only detectable after rhTSH stimulation in their patients.…”
Section: Samplingmentioning
confidence: 99%
“…In particular, there is a large inter-method variability in results with IMAs for serum TgAb despite the introduction of the International Reference Preparation 65/093 (IRP 65/093) [88]. Further confusion may result from the use of different concentrations or cutoff values for defining 'positive' and 'negative' TgAb results [85].…”
Section: Samplingmentioning
confidence: 99%
“…Earlier we listed the proteomic analysis of thyroglobulin as an area where MS can offer clinical benefit compared with immunoassay, due to the interference of autoantibodies. Unfortunately, MS does not provide all the needed answers in these cases because there are reports of image-confirmed disease recurrence that had undetectable concentrations of thyroglobulin by MS (38 ). A closer examination of the technology reveals that many variables need to be controlled to provide an accurate quantitative result.…”
Section: Challenges With Msmentioning
confidence: 99%
“…Serum thyroglobulin is the widely used tumour marker in patients with DTC but its utility is frequently hampered by the presence of antithyroglobulin antibodies [45] . The analysis of thyroglobulin free DNA can bypass the antibodies and provide a non-invasive approach to assess tumour evolution [46] .…”
Section: Molecular Analysismentioning
confidence: 99%